Priority directions of development of transport and logistics infrastructure of Kazakhstan at the present stage - Baibossynov, S.B.; Akenov, S.Sh.; Kasymova, N.Sh. (BUKETOV BUSINESS REVIEW, 2019)
In the article the main directions of further improvement of socio-economic modernization of Kazakhstan are revealed, the role of transport and logistics infrastructure is growing rapidly, taking an international scale and highlighting transport transit as one of the leading functions of the national transport system. In this regard, the priority task for Kazakhstan in the development of the national transport and communication complex is to ensure its competitiveness in the world market of services and, accordingly, to stimulate the growth of transportation of goods through Kazakhstan. The transport system in its current state cannot fully meet the needs of the economy, given the vast territory of Kazakhstan and the ambitious plans of the government for the long-term development of the economic potential of the Republic. The tasks of the upcoming stage of development of the transport industry in Kazakhstan include improving the efficiency of activities, new construction of transport infrastructure, modernization of existing infrastructure, acceleration of goods movement and reduction of transport costs, improvement of the safety and sustainability of the industry, as well as the availability of transport services for the population. Kazakhstan is developing international cooperation in the field of transport, thanks to which the country receives new equipment and technologies, introduces international experience. In this direction, it is necessary to establish the main trends in the development of the international market of logistics services. To determine the directions of influence of integration associations as the Eurasian economic Union and the initiatives of the «Silk Road Economic belt» on the development of transport and logistics infrastructure of Kazakhstan.